The dynamic of Arabic academic writing in postgraduate program: linguistic corpus analysis - Arifa, Zakiyah; Al Faruq, Umar; Hizbullah, Nur; Hassan, Haslina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2022)
This descriptive library research describes the active research topics and methods most interested postgraduate students majoring in Arabic in master's and doctoral degrees. It explains the representation of research dynamic map in Arabic learning supported by corpus linguistic analysis. This research applied two research approaches; the quantitative approach was used to describe the frequency of words used by the postgrad students in their academic writings analyzed by Antconc software. A qualitative approach was used to explain the representation of corpusbased findings. The data are taken from abstracts of Arabic academic writings belonging to one of the Indonesian public universities’ digital libraries. The results showed that students' most popular research topics in the last five years are education topics, namely materials and textbooks development; second, linguistics topics such as naḥwu and tarkīb, and language skills is mahārah kalam. This study shows that students tend to research naḥwu and tarkīb based on speaking skills material. The most widely used students research method was Research and Development (R & R&D). Students tend to develop teaching materials with various perspectives, as R&D was a trend of research method. As a result, students are expected to gain an overview of the dynamic discourse map and research trends in Arabic learning as a foundation or preliminary research to select and determine research topics and methods for the final project. To avoid similarity, plagiarism, and saturation, one must choose variations in topics and types of research methods and follow existing trends.